Peningkatan Kualitas Hidup Pasien Kanker Payudara Melalui Program BESTCARE (Breast Cancer Wound and Palliative Care) - Endah Janitra, Fitria; Wijayanti, Kurnia; Wahyuningsih, Indah Sri; Apriyanti, Hani Werdi (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
The incidence of breast cancer increase every year, if didn’t controlled by the WHO estimates that there will be an increase of 30% and 70% in 2030. The patients often experience are complex problems such as the lack of self-confidence, pain in wounds and aesthetic problems. Postoperative patients or chemotherapy need proper care in order to achieve a good quality of life. The BESTCARE program aims to improve the quality of life of breast cancer patients through activities that can be carried out by cadres and patients. The methods was lectures, demonstrations and practices. While the media used are lectures, demonstrations, practices and wound care. The material presented includes the incidence of breast cancer, understanding, risk factors, conscious examination steps, wound care with modern dressing. Results: The team succeeded in forming a cancer care health, knowledge and understanding of the cadre of mam health increased from 50% to 85%, health cadres were able to make conscious movements from before 55% to 90%, an increase in the number of visits, decreased pain scale and wound care progress with modern dressing. Conclusion: The program of activities carried out by the Bestcare team was able to be carried out properly and as expected improving the quality of life in palliative patients both in the clinic or home visit.